2015
DOI: 10.1128/aem.00465-15
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Escherichia coli Virulence Factors in Dairy Herds and Farm Environments in a Longitudinal Study in the United States

Abstract: g Pathogenic Escherichia coli or its associated virulence factors have been frequently detected in dairy cow manure, milk, and dairy farm environments. However, it is unclear what the long-term dynamics of E. coli virulence factors are and which farm compartments act as reservoirs. This study assessed the occurrence and dynamics of four E. coli virulence factors (eae, stx 1 , stx 2 , and the gamma allele of the tir gene [␥-tir]) on three U.S. dairy farms. Fecal, manure, water, feed, milk, and milk filter sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 98 publications
4
15
2
Order By: Relevance
“…In this study, the intimin eae gene was detected in 8(28.6%) of the E. coli isolates recovered from the milk samples. The finding is consistent with the reports [13,17,31,38,43] with prevalence (100%, 36%, 44.19%, 4.05-13.4%, 18.0%-24.3%) in these locations (Iran, South Africa, USA, Saudi Arabia) respectively. Al-zogibi et al [31] reported eae gene of 10(58.82%) in E. coli isolates from raw beef, E. coli isolates from milk and dairy products in Iran were positive for eae genes [4], E. coli isolates from faecal samples of diarrheic calves [2] and chicken meat [44] were positive for eae gene in Iran.…”
Section: Pcrsupporting
confidence: 92%
“…In this study, the intimin eae gene was detected in 8(28.6%) of the E. coli isolates recovered from the milk samples. The finding is consistent with the reports [13,17,31,38,43] with prevalence (100%, 36%, 44.19%, 4.05-13.4%, 18.0%-24.3%) in these locations (Iran, South Africa, USA, Saudi Arabia) respectively. Al-zogibi et al [31] reported eae gene of 10(58.82%) in E. coli isolates from raw beef, E. coli isolates from milk and dairy products in Iran were positive for eae genes [4], E. coli isolates from faecal samples of diarrheic calves [2] and chicken meat [44] were positive for eae gene in Iran.…”
Section: Pcrsupporting
confidence: 92%
“…STEC was detected in 6.5%, 6%, and 7% of all food, milk, and meat samples, respectively. These findings were higher than those in previous reports (1.9-4.1%) in the USA [31] but lower than reports (10.7-29.7%) from other countries [32][33][34]. STEC isolates were found in 12% of diarrheic cattle samples; higher rates (18.7-53.2%) were reported from another location in Egypt [18] and elsewhere [31,35].…”
Section: Discussioncontrasting
confidence: 63%
“…in bovine manure in various regions in the US. (Hancock et al 1997;Dargatz et al 2000;Alam and Zurek 2006;LeJeune et al 2006;Lambertini et al 2015;Rodriguez-Rivera et al 2016). Jay et al (2007) reported that 26 of 77 (33Á8%) cattle faecal samples collected at a ranch on the central California coast were positive for E. coli O157:H7.…”
Section: Introductionmentioning
confidence: 99%